PECULIARITIES OF THE WORK OF THE CONCERT MASTER OF VOCAL CLASS IN THE CONDITIONS OF DISTANCE LEARNING - Міщенко, С. П. (SWorldJournal, 2022)
The article analyzes the peculiarities of the use of information technologies in the performance of the accompanist . It is noted that it is expedient to involve the software for recording the musical material during the rehearsal process for its further